Weed dynamics, wheat (Triticum aestivum) yield and irrigation water-use efficiency under conservation agriculture - SHARMA, TARUN; DAS, T K; SUDHISHRI, SUSAMA; MAITY, PRAGATI PRAMANIK; BISWAS, SUNANDA; GOVINDASAMY, PRABHU; RAJ, RISHI; SEN, SUMAN; SINGH, TEEKAM; PAUL, AMRIT KUMAR; ROY, ARKAPRAVA; SAHA, PRIYANKA; et al. (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted to evaluate the impacts of a 12-year old conservation agriculture (CA)- based pigeon pea-wheat system on weeds, wheat crop, and resource use during winter (rabi) 2021–22. Results indicated that surface retention of residue irrespective of ZT permanent bed and N dose led to significant reduction in weed interference at 60 DAS. CA-based systems reduced weed density and dry weight considerably than CT. CA- based systems led to significantly higher wheat grain yield (by 11.6–14.9%) and net B:C (by 24.0 –28.0%) than CT, and PFBR100N and PBBR100N were slightly superior to others. PBBR100N and PBBR75N had lower irrigation water use and significantly higher irrigation water productivity than CT. Contrast analysis showed that wheat yield and water productivity were comparable between 75% N and 100% N in CA, indicating a saving of 25% N under CA.